Stepping into the first public policy research journal - Upreti, Bishnu Raj (Nepal Public Policy Review, 2021)
We are pleased to launch the first-ever policy journal – Nepal Public Policy Review (NPPR) – in Nepal. It focuses on a wide spectrum of policy domains but is especially aimed at enhancing an interface between academic research and public policy-making. To this end, it collects research-based evidence as well as ideas and experiences of policy practitioners and policy advocates that can be tapped for policy-making processes.